2017
DOI: 10.1111/obr.12564
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal discrimination and markers of adiposity in longitudinal studies: a systematic review

Abstract: While the impact of interpersonal discrimination on mental health is well established, its effects on physical health outcomes have not been fully elucidated. This study systematically reviewed the literature on the prospective association between interpersonal discrimination and markers of adiposity. Medline, Web of Science, Scopus, PsycInfo, SciELO, LILACS, Google Scholar, Capes/Brazil and ProQuest databases were used to retrieve relevant information in November 2016. The results from the 10 studies that met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…A 2017 review of 10 longitudinal studies found evidence of a consistent association between self‐reported discrimination and body mass index (BMI), waist circumference, and incidence of obesity . The associations between experiences of discrimination and adiposity were predominantly linear, and racial discrimination was also significantly associated with changes in BMI and waist circumference among women, but not men.…”
Section: Resultsmentioning
confidence: 99%
“…A 2017 review of 10 longitudinal studies found evidence of a consistent association between self‐reported discrimination and body mass index (BMI), waist circumference, and incidence of obesity . The associations between experiences of discrimination and adiposity were predominantly linear, and racial discrimination was also significantly associated with changes in BMI and waist circumference among women, but not men.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that experiencing discrimination had a significant impact on the psychosocial determinants of health, but not physical health. There is a large body of evidence that reports the relationship between perceived discrimination on physical health problems including hypertension ( Dolezsar et al, 2014 ), cardiovascular disease and inflammation ( Stepanikova et al, 2017 ) and related factors, such as poor sleep ( Slopen et al, 2016 ), obesity ( Bernardo et al, 2017 ), and alcohol use ( Gilbert & Zemore, 2016 ). Discrimination has also been linked with decreased health care seeking behaviors and adherence to medical recommendations among those who experience it ( Williams et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Racial discrimination is a social stressor that racial and ethnic minority people are commonly exposed to in the United States. By putting chronic strain on the autonomic nervous system, exposure to discriminatory events has been linked to numerous negative psychological and physical health outcomes, including psychological distress (Berger & Sarnyai, 2015; Chae et al., 2016; Priest et al., 2013), low birth weight (Alhusen et al., 2016), cardiovascular disease and hypertension (Chae et al., 2010, 2012; Dolezsar et al., 2014; Lewis et al., 2014; Orom et al., 2017; Udo & Grilo, 2017), obesity (de Bernardo et al., 2017), leukocyte telomere length (Chae et al., 2016), and oxidative stress (Szanton et al., 2012). Specific exposures to discrimination and other racism‐related experiences are characterized as acute social stressors that activate biological stress responses, but which accumulate over time when chronic to accelerate disease and aging processes (Goosby & Heidbrink, 2013; Harrell et al., 2011).…”
Section: Introductionmentioning
confidence: 99%